2018
DOI: 10.1111/jomf.12504
|View full text |Cite|
|
Sign up to set email alerts
|

Loose Ties? Determinants of Father–Child Contact After Separation in Germany

Abstract: Objective: This article examines the determinants of father-child contact in Germany after divorce and separation, with a special emphasis on the role of legal child support. Background: The contact separated fathers have with their children is a policy-relevant issue that has been intensively addressed in previous research for the United States, the United Kingdom, and Canada. For continental Europe, there has been far less research on this topic. This article investigated how fathers' union status at childbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 34 publications
2
32
0
3
Order By: Relevance
“…The majority of research on this topic focuses mainly on the frequency and quality of face-to-face visitation between nonresident parents and their children (K€ oppen, Kreyenfeld, and Trappe 2018, Szalma and R ekai 2019, Westphal, Poortman, and van der Lippe 2014. Although there have been some studies that explored communication online or via telephone (Marryat, Reid, and Wasoff 2009;Hughes and Funston 2006;Leite and McKenry 2002), they remained marginal.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research on this topic focuses mainly on the frequency and quality of face-to-face visitation between nonresident parents and their children (K€ oppen, Kreyenfeld, and Trappe 2018, Szalma and R ekai 2019, Westphal, Poortman, and van der Lippe 2014. Although there have been some studies that explored communication online or via telephone (Marryat, Reid, and Wasoff 2009;Hughes and Funston 2006;Leite and McKenry 2002), they remained marginal.…”
Section: Introductionmentioning
confidence: 99%
“…One of the factors that has been identified as being most important for child well‐being after family dissolution is the involvement of the father. It is a worldwide phenomenon that in the majority of families, children stay with their mothers after parental break up and suffer from less contact or even no contact and involvement with their fathers (e.g., Holt, 2016; Kalmijn, 2015; Köppen, Kreyenfeld, & Trappe, 2018). However, it has been shown that the involvement of fathers after family dissolution has positive effects on children’s well‐being in many respects (e.g., Adamsons & Johnson, 2013; Beckmeyer, Stafford Markham, & Troilo, 2019; Kalmijn, 2016; Poortman, 2018).…”
mentioning
confidence: 99%
“…The implications for the nature of parent–child ties have been profound, as multiple biological parents and stepparents may have to coexist and coordinate their relations with a child (Ganong & Coleman, ). Thus far, particular interest has been directed to the disadvantaged position of divorced fathers in the development of close ties with their children (Hetherington, ; Kalmijn, ; Kalmijn, ; Köppen, Kreyenfeld, & Trappe, ). The emphasis on divorced fathers is partially driven by the fact that mothers generally assume a primary caretaking role after parental divorce, while fathers often become less involved in childcare (Allen & Hawkins, ).…”
mentioning
confidence: 99%